THE EFFECT OF THE REACTIVE ELEMENT ON THE CHROMOXIDE AND ALUM IN IDE LAYERS IN THE HIGH TEMPERATURE CONDITION - Mohammad Dani; Nurdin Effendi (PTBIN-BATAN)
THE EFFECT OF THE REACTIVE ELEMENT ON THE CHROMOXmE AND ALUMINmE LAYERS IN THEHIGH TEMPERATURE CONDITION. Oxide layers at high temperature condition, as Cr203' A12O3. growing act not only ascorrosion barrier, but also as a diffusion barrier of agressive components. MA956 and Ni75Cr25 alloy were studied to observethe effect of yttrium coating on their oxidation behavior. The influence of these coatings on the oxidation behaviour of the alloywas studied. Thin coatings of Yttrium have been applied to the surface of those alloys by vacuum coating. The growth of theoxide layers under controlled has been investigated in this work by Analytical Transmission Electron Microscope (ATEM) andScanning Electron Microscopy (SEM). It was found that addition of small amounts of elements such as Yttrium to these alloysgreatly increase their oxidation resistance.